(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the authors examine the system of evidence in a criminal case, the subject of proof in the case, check the items of evidence, and the viewpoints of various authors on the subject. Key words: evidence, circumstantial evidence, proof system, circumstances, verification of proofs.